Pengaruh Asimetri Informasi, Insentif Pajak, Risiko Litigasi, Ukuran Perusahaan Dan Financial Distress Terhadap Prudence Akuntansi (Studi Pada Perusahaan Sektor Property and Real Estate Yang Terdaftar di Bursa Efek Indonesia Periode 2021-2023) - Randy Hardian; Gustati Gustati; Armel Yentifa (Politeknik Raflesia Press, 2025)
This study aims to examine the influence of information asymmetry, tax incentives, litigation risk, company size, and financial distress on accounting prudence. This research employs a quantitative approach. The sample was obtained using purposive sampling, selecting samples based on predetermined criteria. The purposive sampling resulted in 130 observation data from property and real estate companies listed on the Indonesia Stock Exchange (IDX) during the 2021–2023 period. The analytical method used is multiple linear regression with SPSS version 25. The results of this study indicate that, partially, information asymmetry, tax incentives, litigation risk, company size, and financial distress have an effect on accounting prudence. Simultaneously, information asymmetry, tax incentives, litigation risk, company size, and financial distress affect accounting prudence.